PERANCANGAN SISTEM ADMINISTRASI PEMBELAJARAN SEMPOA SIP KEPRI BERBASIS WEB - Filza, Nurul; Hutabri, Elbert (LPPM Universitas Putera Batam, 2025)
The rapid development of education demands high-quality, competent, and competitive human resources. The community in Batam City supports this by initiating activities such as abacus lessons (sempoa), which enhance children's arithmetic skills, logical thinking, concentration, and memory. In education management, school administration plays a vital role in improving services and performance. With technological advancements, administrative processes have shifted from manual methods to digital solutions, such as Excel-based and web-based applications. Web-based systems, in particular, enable efficient, integrated, and accurate data management, supporting a more modern and effective school administration system.